2002
DOI: 10.1149/1.1512672
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Porous TiO[sub 2] by Immersing Ti in NaOH Solution

Abstract: The formation of a porous TiO 2 layer by immersing Ti in 5 M NaOH at 303 K was investigated using electrochemical measurements, a scanning electron microscope, and grazing incident X-ray diffraction. The porous layer was readily obtained in the case of the presence of titanium hydride (TiH 2 ) on the surface before immersion. The crystalline structure of the porous layer is composed of a mixture of the rutile and anatase type TiO 2 . The porous layer is hard to produce without the presence of TiH 2 . The TiH 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 11 publications
5
55
0
Order By: Relevance
“…Fig. 2 (a), (b), and (c) show the pore morphology that formed on the surface of the Ti disk, and many researchers have reported that such a morphology can only be obtained when Ti is immersed into an NaOH solution [12,13]. The increase in temperature during heat treatment densifies the pores and changes them into rod-like features.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 2 (a), (b), and (c) show the pore morphology that formed on the surface of the Ti disk, and many researchers have reported that such a morphology can only be obtained when Ti is immersed into an NaOH solution [12,13]. The increase in temperature during heat treatment densifies the pores and changes them into rod-like features.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a nanoporous and thick titanium oxide surface can induce bony ingrowth into the porous structure, resulting in morphological fixation of the implants to the bone [8][9][10]. Previously, numerous procedures for forming titanium oxide films have been examined [8][9][10][11][12][13][14]. Among them, anodization is very popular.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, metal-based implants are recommended for use as coatings on bloodcontacting implants. The adhesion of blood cells on various implants with smooth and rough surfaces following surface treatment has been discussed elsewhere [22,23]. Cell adhesion was higher on rougher surfaces, with a Ra in the range 0.2-0.5 mm [24].…”
Section: Resultsmentioning
confidence: 99%